Programmes to support transitions in care for children and youth with complex care needs and their families: a scoping review protocol. Issue 6 (21st June 2020) - Doucet, Shelley; Curran, Janet A; Breneol, Sydney; Luke, Alison; Dionne, Emilie; Azar, Rima; Reid, Amy E; McKibbon, Shelley; Horsman, Amanda R; Binns, Krystal
Abstract : Introduction: Children and youth with complex care needs (CCNs) and their families experience many care transitions over their lifespan and are consequently vulnerable to the discontinuity or gaps in care that can occur during these transitions. Transitional care programmes, broadly defined as one or more intervention(s) or service(s) that aim to improve continuity of care, are increasingly being developed to address transitions in care for children and youth with CCNs. However, this literature has not yet been systematically examined at a comprehensive level. The purpose of this scoping review is to map the range of programmes that support transitions in care for children and youth with CCNs and their families during two phases of their lifespan: (1) up to the age of 19 years (not including their transition to adult healthcare) and (2) when transitioning from paediatric to adult healthcare. Methods and analysis: The Joanna Briggs Institute methodology for scoping reviews (ScR) will be used for the proposed scoping review. ScR are a type of knowledge synthesis that are useful for addressing exploratory research questions that aim to map key concepts and types of evidence on a topic and can be used to organise what is known about the phenomena. A preliminary search of PubMed was conducted in December 2018. Ethics and dissemination: Ethical approval is not required where this study is a review of the published and publicly reported literature. The research team's advisory council will develop a research dissemination strategy with goals, target audiences, expertise/leadership, resources and deadlines to maximise project outputs. The end-of-grant activities will be used to raise awareness, promote action and inform future research, policy and practice on this topic.